2008
DOI: 10.1007/s11589-008-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic study on SS waveform splitting and complication

Abstract: Some influential factors on the complication of SS waveform (with epicentral distance within 40°∼180°) are analyzed quantitatively by calculating the full-wave synthetic seismogram using propagation matrix method. Our results show that the transmission-conversion and reflection-conversion phases of S wave at the interface of Moho and free surface beneath bounce points are mainly responsible for the complication of SS waveform, the velocity contrast between the two sides of Moho boundary under SS bounce point a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, these leave the asthenospheric flow undetected. SS wave splitting has been used to constrain anisotropic behaviors beneath SS bounce points in the upper mantle (Wolfe & Silver, ), but SS waveforms appear to be disturbed by crustal reverberations beneath SS bounce points (He et al, ; Rychert & Shearer, ). Phase pairs like S‐SS , S‐sS , ScS‐sScS , and ScS‐ScSScS have been used to isolate the upper mantle anisotropy beneath surface bounce points by removing the contributions from anisotropy in the upper mantle beneath stations and sources (e.g., Farra & Vinnik, ; Fischer & Yang, ; Vinnik & Farra, ; Yang & Fischer, ), but source, bounce point, and receiver splitting should be carefully considered in a proper order (Wolfe & Silver, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these leave the asthenospheric flow undetected. SS wave splitting has been used to constrain anisotropic behaviors beneath SS bounce points in the upper mantle (Wolfe & Silver, ), but SS waveforms appear to be disturbed by crustal reverberations beneath SS bounce points (He et al, ; Rychert & Shearer, ). Phase pairs like S‐SS , S‐sS , ScS‐sScS , and ScS‐ScSScS have been used to isolate the upper mantle anisotropy beneath surface bounce points by removing the contributions from anisotropy in the upper mantle beneath stations and sources (e.g., Farra & Vinnik, ; Fischer & Yang, ; Vinnik & Farra, ; Yang & Fischer, ), but source, bounce point, and receiver splitting should be carefully considered in a proper order (Wolfe & Silver, ).…”
Section: Introductionmentioning
confidence: 99%
“…Observations and analyses have shown that when the signal originates from the high-altitude ionosphere (magnetosphere), the ULF magnetic field polarization value Y zh is usually less than 1, whereas the ULF magnetic field polarization value Y zh from seismogenic regions is ≥1; therefore, the polarization value is considered the key to differentiating between geomagnetic radiation originating from the ionosphere (magnetosphere) and seismic magnetic radiation originating from subsurface rocks (e.g., [18,[33][34][35]). In addition, precursory anomalies are usually indicated by high vertical intensity polarization ratio values (Y zh ≥ 1), while the postearthquake effects of geomagnetic observations are usually distinguished by the reduction in (recovery of) the vertical intensity polarization ratio to a normal range (Y zh < 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, fragmentary trilobate leaves with basal actinodromous venation and regularly spaced marginal teeth assigned to Liquidambar sp. were reported from the Eocene of China [ 51 , 52 ]. Recently, three Liquidambar species, L. maomingensis [ 30 ], L. bella N. Maslova et Kodrul [ 31 ], and L. hainanensis [ 32 ], were described from the Eocene of South China.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, co-occurrences of Liquidambar leaves and reproductive structures are of considerable interest [ 18 , 22 , 30 , 32 , 33 , 50 ]. In China, altingioid megafossils are known from the Eocene [ 30 , 31 , 32 , 51 , 52 , 53 ], Miocene [ 7 , 28 , 33 , 50 , 54 ], and Upper Pleistocene [ 54 ]. Until now, megafossils of Liquidambar from the Oligocene of China have not been reported.…”
Section: Introductionmentioning
confidence: 99%